2022
DOI: 10.2147/dddt.s366622
|View full text |Cite
|
Sign up to set email alerts
|

Prostate Cancer Therapy Using Docetaxel and Formononetin Combination: Hyaluronic Acid and Epidermal Growth Factor Receptor Targeted Peptide Dual Ligands Modified Binary Nanoparticles to Facilitate the in vivo Anti-Tumor Activity

Abstract: Objective To evaluate the prostate cancer therapy efficiency of the synergistic combination docetaxel (DTX) and formononetin (FMN) in one nano-sized drug delivery system. Hyaluronic acid (HA) and epidermal growth factor receptor-targeted peptide (GE11) dual ligands were applied to modify the nano-systems. Methods In this study, GE11-modified nanoparticles (GE-NPs) were applied for the loading of DTX, and HA-decorated NPs (HA-NPs) were used to encapsulate FMN. HA and GE1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 45 publications
0
11
0
Order By: Relevance
“…In this study, we found that drug release from AP/Tf-Drn/Lut NPs was slower than single ligand (AP or Tf)–decorated systems, which could be construed as more ligands the surface of the NPs perhaps reducing the release rate. The decoration of ligands on the surface of NPs may affect drug-release behavior due to their hindering effect, as concluded by Dong et al 39 The reason that drug release could not reach 100% may be due to the matrix of NPs hindering some drug release.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…In this study, we found that drug release from AP/Tf-Drn/Lut NPs was slower than single ligand (AP or Tf)–decorated systems, which could be construed as more ligands the surface of the NPs perhaps reducing the release rate. The decoration of ligands on the surface of NPs may affect drug-release behavior due to their hindering effect, as concluded by Dong et al 39 The reason that drug release could not reach 100% may be due to the matrix of NPs hindering some drug release.…”
Section: Discussionmentioning
confidence: 98%
“…38 Dong et al developed hyaluronic acid-and EGFR-targeted dual peptide ligand-modified docetaxel-formononetin NPs to facilitate prostate cancer therapy. 39 In the present research, we developed AP/Tf-Drn/Lut NPs for leukemia therapy. AP/Tf-Drn/Lut NPs were 187 nm in size.…”
Section: Discussionmentioning
confidence: 99%
“…Formonetin (FMN) is an effective ingredient extracted from Trifolium pratense and Astragalus membranaceus, which can be used to treat castration-tolerant prostate cancer ( Tay et al, 2019 ). To improve the synergistic anti-cancer effects, Dong et al ( Dong et al, 2022 ) used HA and GE as the carrier of FMN and DTX, respectively, and self-assembled the two carriers to prepare binary nanoparticles (HA/GE-DTX/FMN NP). The results showed that the particle size of HA/GE-DTX/FMN nanoparticles was 190 nm, and the zeta potential was 20 mV.…”
Section: Polymer-based Nanocarriers For Co-deliverymentioning
confidence: 99%
“…These hydroxyls are also able to chelate metal ions and, thus, hamper the metal-catalyzed generation of reactive oxygen substances (ROS) and their oxidant activity. According to our research of the literature, the flavonoids that have been included in HA-coated delivery nanosystems investigated against cancer in the last 5 years are the two flavonols: kaempferol [34] and quercetin (QU) [35][36][37][38][39][40][41], the flavanol epigallocatechin-3-gallate (EGCG) [42][43][44][45][46][47] the flavanone naringenin [48], the isoflavone formononetin [49], and a mix of anthocyanins extracted from corn [50]. Between brackets are reported the number of compounds belonging to each class or subclass according to this classification.…”
Section: Phecs Included In Drug Nanodelivery Systems For Tumor Targetingmentioning
confidence: 99%
“…Thus, in this case, QU was the only anticancer agent delivered to the very aggressive 4T1 triple-negative breast cancer (TNBC) mouse cells grown in vitro or transplanted in syngeneic immunocompetent Balbc/mice. In vitro: ↓ PC3 cell viability In vivo: ↓ Tumor volume ↑ Drug distribution in tumor [49] CD/QU: 2-hydroxypropyl-β-cyclodextrin/Quercetin; CTGF: connective tissue growth factor; CU: curcumin; DOX: doxorubicin; DXT: docetaxel; EGCG: epigallocatechin-3-gallate; HA: hyaluronic acid; KA: kaempferol; MDR: multidrug resistance; NP: nanoparticles; PEI-TOS/HA-QU: Polyethyleneimine-Tocopherol Hydrogen Succinate/Hyaluronic Acid-Quercetin; PTX: paclitaxel; QU: Quercetin; TPGS: D-Alpha-tocopheryl polyethylene glycol 1000 succinate.…”
Section: Ha-based Nanocarrier Systems Loading Flavonoidsmentioning
confidence: 99%